Global Research Trends on Infertility and Psychology From the Past Two Decades: A Bibliometric and Visualized Study - Zhu, Hongkun; Shi, Lingli; Wang, Rong; Cui, Lijuan; Wang, Jiahui; Tang, Mengyu; Qian, Haiqing; Wei, Minggang; Wang, Lihong; Zhou, Huifang; Xu, Wenting (Frontiers in Endocrinology, 2022)
Objectives: The aim of this study was to evaluate the global scientific output of research on infertility and psychology; explore the current status and trends in this field through the cooperation of authors, countries, and institutions; shed light on the direction of clinical infertility research in the future; and provide inspiration for targeted diagnosis and treatment of infertility. Methods: Research publications on infertility and psychology were retrieved from the Web of Science Core Collection (WoSCC). Bibliometric analyses were performed using VOSviewer software and the bibliometrix R package. Network maps were generated to evaluate the collaborations between different authors, countries, institutions, and keywords. Results: A total of 151 articles related to the study of infertility and psychology were identified. We observed a gradual increase in the number of publications from 2001 to 2021, and the trend has been relatively stable in the past 8 years. Human Reproduction (England), as the leading journal publishing the most papers (29 articles), was cited in the most journals (1208 times). Boivin J was the most prolific author (16 articles), with the largest numbers of citations (890 times) and the highest h-index (14) during the past decades. Boivin J was also the leader with the highest publication frequency and more active cooperation with other top authors. The United Kingdom (34 papers) and Cardiff University (25 articles) contributed the most publications and were the leading contributors in this field. Active cooperation between countries and between institutions was observed, and analyses of articles and references were also shown. The main hot topics included matters related to women (39 times), in-vitro salt (31 times), infertility (30 times), couples (25 times), and impact (24 times). Conclusion: Our study results provide a comprehensive overview of the development of scientific literature, allowing relevant authors and research teams to recognize the current research status in this field. At the same time, infertility and psychology may soon become hotspots and should be closely monitored.